The Tax Responsible Party of Corporate Taxpayer on Legal Liability Discourse - Johan, Arvie (Media Iuris, 2025)
This article examines, from the perspective of legal liability, the determination of third party liability other than corporate taxpayers, both personally and jointly. The discussion covers three areas, including tax provisions, tax court decisions, and the concept of legal liability. The results are, firstly, the third party liability of corporate taxpayers is the target of Compulsion Letters, Seizures, and Auctions, both personally and jointly. Secondly, several tax court lawsuit decisions indicate that in principle the obligation of corporate taxpayers to pay tax debts is attached to the third party liability, and for director, this attachment opens up the possibility of interference with his/her ownership rights. Finally, the provisions on the third party liability of corporate taxpayers are not rooted in the concept of legal liability, thus creating a risk of uncertainty as shown in the tax court lawsuit decision.